Strategy Management Enhancement Quality Record Medical Electronic In Hospital - Cecilia Farrona Al Hadri; Arifah Damayanti; Salma Santiya Wulandari; Wella Niki Putri; Puput Lestari (Pusat Riset dan Inovasi Nasional, 2022)
Improving quality is a very important factor in the field of hospital services, with good quality the level of service it will improve the quality of service. Quality of health services as the degree or level of perfection of health services carried out in accordance with applicable service standards. One of them is the medical record service. The purpose of this theoretical review is to determine management strategies for improving the quality of medical records in hospitals. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are the management strategies that need to be carried out, namely the dimensions of health services which include reliability, responsiveness, assurance, empathy, and tangibles. Medical record is a statement both written and recorded regarding identity, anamnesis, laboratories physical determinations, diagnosis of all medical services and actions provided to patients, and treatment whether inpatients, outpatient or emergency department.